Inventory Control of Drugs Listed in Private Health Insurance at Pharmacies in South Tangerang using ABC Analysis - Andriyani R. Fahriati; Dwi S. Suryatiningrum; Tanti J. Saragih (Universitas Padjadjaran, Indonesia, 2021)
Inventory control in pharmacies must be appropriately and effectively maintained to promote continuous drug affordability and availability in the community within the healthcare delivery system. Initially, effective drug planning and procurement are essential to attain proper drug selection, quantification, and procurement based on the consumption pattern with good economic impact and clinical value. Therefore, the ABC analysis method is suggested to be implemented to optimize efficient budget and effective drug planning. This study aimed to investigate the planning and procurement process of drug listed in private health insurance using the ABC analysis method in the pharmacies X and Y. This study was non-experimental study with descriptive analysis utilizing qualitative and quantitative data. Drug enlisted in the private insurance data in 2019 were taken retrospectively. Based on the ABC analysis results, in pharmacy store X, drug listed in group A showed 83 items with the highest investment value of 86.38%, group B showed 102 items with 15.61%, and group C showed 129 items with the lowest investment value of 4.79%. Meanwhile, in pharmacy Y, drug listed in group A showed 87 items with the highest investment value of 89.62%, group B showed 100 items with 7.62%, and group C showed 134 items with the lowest investment value of 2.76%. Using the ABC analysis to manage the drug inventory system could assist pharmacy store X and Y in planning the procurement of drug listed in the private healthcare insurance effectively. Also, taking into account the values of consumption and investment are obtained efficiently.